DIFFERENTIATION OF DROSOPHILA-SERIDO (ISOFEMALE LINE A95F3) AND D-KOEPFERAE (ISOFEMALE LINE B20D2) - REPRODUCTIVE ISOLATION, DEVELOPMENT TIME AND POLYTENE CHROMOSOME-BANDING PATTERNS - Madiravazzi, L.; Bicudo, HEMD (Soc Brasil Genetica, 1992)
Drosophila serido is considered to be a superspecies consisting of two species: D. serido, from Brazil and D. koepferae from Argentina and Bolivia. However this probably does not express the entire evolutionary complexity of its populations. Isofemale lines A95F3 (from Brazil) and B20D2 (from Argentina), at present representing, respectively, the first and second species, were analyzed for fertility and fecundity in pair-mating intracrosses and intercrosses, as well as for development time, banding patterns and asynapsis of polytene chromosomes in the isofemale lines and their hybrids.Although variations in experimental conditions resulted in some variability in the results, in general A95F3 fertility and fecundity were lower than in B20D2. Intercrosses of A95F3 females and B20D2 males showed lower fertility and fecundity than the reciprocal crosses, following more closely characteristics of the mother strains. This is in contrast to the results obtained by Fontdevilla et al. (An. Entomol. Soc. Amer. 81: 380-385, 1988) and may be due to the different geographic origin of D. serido strains they used in crosses to B20D2. This difference and others cited in the literature relative to aedeagus morphology, karyotype characteristics, inversion polymorphisms and reproductive isolation strongly indicate that A95F3 and D. serido from the State of Bahia, Brazil are not a single evolutionary entity, reinforcing the idea of greater complexity of the superspecies D. serido than is known today.The reproductive isolation mechanisms found operating between A95F3 and B20D2 were prezygotic and postzygotic, the latter included mortality at the larvae stage in both directions of crosses and sterility of male hybrids in intercrosses involving B20D2 females and A95F3 males. The two isofemale lines differed in egg-adult development time, which was also differently affected by culture medium composition.A95F3 and B20D2 also showed differences in the banding patterns of proximal regions of polytene chromosomes 2, 3 and X, a fixed inversion in chromosome 3 (here named 3t), apparently not described previously, and a high degree of asynapsis in hybrids.These observations, especially those related to reproductive isolation and chromosomal differentiation (including the karyotype, previously described, and the differentiation of banding patterns, described in this paper), as well as the extensive asynapsis observed in hybrids reinforces the distinct species status of A95F3 and B20D2 isofemale lines.